The Effectiveness of the Mentimeter-Based 5E Model in Islamic Religious Education - Risdiani, Risdiani; Raharjo, Raharjo; Saminanto, Saminanto; Warsiyah, Warsiyah; Qutni, Darul; Rizkillah, Rijal Wakhid; Setianto, Gigih (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study examines the effectiveness of integrating the 5E learning model with the Mentimeter application in enhancing students’ critical and creative thinking skills in Islamic Religious Education courses at three universities in Semarang. Using a quantitative pre-experimental design with a multi-group pretest–posttest structure, the study involved 133 first-semester students from three universities selected through purposive sampling with a minimum attendance criterion of 80%. The data were drawn from pretest and posttest scores obtained through essay-type test instruments, with data collection carried out at the beginning and the end of the semester. Data were analyzed using paired statistical tests (Paired Sample t-Test and Wilcoxon Signed Rank Test), N-Gain calculations, and the Kruskal–Wallis test to examine the consistency of improvement across institutions. The findings indicate significant increases in critical thinking skills (N-Gain = 0.48) and creative thinking skills (N-Gain = 0.40) with a high level of significance (p < 0.01). These improvements were consistent across universities with different institutional characteristics (p > 0.05), indicating that the 5E syntax based on Mentimeter is robust and adaptive to various learning contexts. The results suggest that technology-based contextual learning can bridge the gap between traditional religious instruction and the cognitive demands of the Society 5.0 era. This study offers a new pedagogical framework for religious education by combining structured inquiry stages with interactive digital technology, and recommends further research employing longitudinal or experimental designs that consider variables such as digital literacy, learning styles, and socio-economic background.